Perlindungan Hukum bagi Investor : Tanggung Jawab Perusahaan dalam Pasar Modal - Michelle Marvella Santosa; Veronica Advlin Agnesia (Jurnal Hukum Lex Generalis, 2025)
The capital market plays an important role in the economy as a means for companies to obtain capital and investors to develop assets. Legal protection for investors is a crucial aspect to maintain market confidence and stability. This article discusses the role of Law No. 8/1995 on Capital Markets in protecting investors through information disclosure obligations, good corporate governance, and dispute resolution mechanisms. In addition, the responsibility of companies in ensuring transparency and accountability is explained as an effort to build investor confidence and create a healthy, transparent and sustainable capital market.